Tekst jako wspólny przedmiot badań teorii tekstu, stylistyki i poetyki - Witosz, Bożena (Stylistyka, 1998)
In this paper the author tries to present various concepts oftext in the latest theories of textual linguistics, stylistics and poetics. In the first part of the study the author indicates basic aspects of a statement (text) worked out on the basis oflinguistic research: comprehensive character ofthe statement; arrangement (in structural, semantic and pragmatic plane); coherence (hiérarchisation of structure); location of the statement in a pragmatic, cultural and historical context. In the next part the author pays attention to distinct approximation of competence and methodology scopes ofthe modem stylistics to the text theory. She enumerates those re[1]search fields for which text theory is a source of inspiration in stylistic analysis which are more completely analysed by stylistics (because of its interdisciplinary character) than by linguistics. Showing text concepts presented by poststructural trends in modem poetry the author draws forth those aspects which in comparison to a linguistic pattern create opposition: structure -texture; relationships of coherence (intratextual) -intertextual relationships; the subject as the central point-lack ofa merging institution; consciousness ofthe act of reading (interpretation of a text) - reading of incorrect interpretations (misreading), reading of a text; text formation as an act of a conscious choice (creation) - writing as quoting (reproduction). In conclusion the author states that the methodological syncretism oftoday will un[1]doubtedly contribute to an elaboration of a comprehensive interdisciplinary theory of text in the future.